Risk Factors for Seizures Among Young Children Monitored With Continuous Electroencephalography in Intensive Care Unit: A Retrospective Study - Vlachy, Jan; Jo, Mingyoung; Li, Qing; Ayer, Turgay; Keskinocak, Pinar; Swann, Julie; Olson, Larry; Vats, Atul (Frontiers in Pediatrics, 2018)
OBJECTIVE: cEEG is an emerging technology for which there are not clear guidelines for patient selection or length of monitoring. The purpose of this study was to identify subgroups of pediatric patients with high incidence of seizures. STUDY DESIGN: We conducted a retrospective study on 517 children monitored by cEEG in the intensive care unit of a children’s hospital. The children were stratified using an age threshold selection method. Using regression modeling, we analyzed significant risk factors for increased seizure risk in younger and older children. Using two alternative correction procedures, we also considered a relevant comparison group to mitigate selection bias and to provide a perspective for our findings. RESULTS: We discovered an approximate risk threshold of 14 months: below this threshold, the seizure risk increases dramatically. The older children had an overall seizure rate of 18%, and previous seizures were the only significant risk factor. In contrast, the younger children had an overall seizure rate of 45%, and the seizures were significantly associated with hypoxic-ischemic encephalopathy (HIE; p=0.007), intracranial hemorrhage (ICH; p=0.005), and central nervous system (CNS) infection (p=0.02). Children with HIE, ICH, or CNS infection accounted for 61% of all seizure patients diagnosed through cEEG under 14 months. CONCLUSIONS: An extremely high incidence of seizures prevails among critically ill children under 14 months, particularly those with HIE, ICH, or CNS infection.